Response Surface Methodology Calibration for Dem Study of the Impact of a Spherical Bit on a Rock - Cruchaga-Ssa., M (Elsevier B.V., 2022)
The discrete element method (DEM) is frequently used for the numerical analysis of rock fractures. The DEM model requires the specification of microparameters that cannot be measured and are not directly related to the macroscopic properties of the material. Therefore, a calibration process for the microparameters is required to simulate the rock behavior. Since the calibration is usually performed iteratively using the trial and error method, several DEM simulations are run. Therefore, the calibration process is computationally expensive. In this work, we propose a calibration method based on the response surface methodology (RSM) that significantly reduces the numerical simulations to be performed during the calibration process, and thus, the associated computational cost. This methodology is novelty applied to impact problems and, it is validated by means of a benchmark, the good agreement obtained between the predicted and observed results verifies the applicability of the proposed method. A force-penetration curve is obtained through this approach, and the energy–time history is plotted. Moreover, several samples are tested to demonstrate the robustness of the solution. The effect of the stress wave under infinite boundary condition is studied. The method is capable of capturing the stress wave movement, and the velocity of the stress wave computed from the numerical results is in good agreement with experimental data. © 2022 Elsevier B.V.